Réfugiés et déplacés dans l’Est du Tchad - Johanne Favre (EchoGéo)
A joint UNO/EU mission is expected in Eastern Chad in November 2007, to guard the camps which hold 230 000 refugees from Darfur and 180 000 displaced Chadians. But the continued rebellions in the region highlight the absence of a settlement to the political crisis in Chad. Moreover, the attempt to guard may run up against the violence spreading through society.